2016
DOI: 10.1016/j.celrep.2016.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomic Analysis of Human Erythropoiesis

Abstract: SUMMARY Mass spectrometry-based proteomics now enables the absolute quantification of thousands of proteins in individual cell types. We used this technology to analyze the dynamic proteome changes occurring during human erythropoiesis. We quantified the absolute expression of 6,130 proteins during erythroid differentiation from late burst-forming units-erythroid (BFU-Es) to orthochromatic erythroblasts. A modest correlation between mRNA and protein expression was observed. We identified several proteins with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
266
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 202 publications
(295 citation statements)
references
References 37 publications
24
266
0
5
Order By: Relevance
“…Strikingly however, PELO was initially up-regulated ~5-fold in the 2 days following hemin induction in K562 cells (Figure 3B–D) and more modestly in published quantitative mass spectrometry data from erythropoietic differentiation of primary CD34+ cells (Fig. 3F) (Gautier et al, 2016). …”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Strikingly however, PELO was initially up-regulated ~5-fold in the 2 days following hemin induction in K562 cells (Figure 3B–D) and more modestly in published quantitative mass spectrometry data from erythropoietic differentiation of primary CD34+ cells (Fig. 3F) (Gautier et al, 2016). …”
Section: Resultsmentioning
confidence: 70%
“…Indeed, we found that the levels of the canonical ribosome recycling factor ABCE1 (Pisarev et al, 2010) are strongly reduced in platelets compared to precursor megakaryoblast cells (Meg01) and in reticulocytes when compared to undifferentiated K562 cells (Figure S2C). Moreover, declining ABCE1 levels have been observed in proteomic analyses of erythroid differentiation from primary human cells (Gautier et al, 2016; Prenni et al, 2012), although the consequences of this decline were not explored. Interestingly, ABCE1 is also depleted in PLPs (Figure 3A) and in K562 cells induced toward erythroid differentiation (Figure 3B–C), where RNA levels also decline (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We explored the expression of erythroid membrane proteins by performing a proteomic analysis of red blood cell ghosts from three PV patients and two age-matched controls (CT) using iTRAQ labeling technology. 8 Red blood cell ghosts were prepared by hypotonic lysis of washed cells as described elsewhere, 9 and peptides were prepared from 100 µg of total membrane proteins by trypsin digestion. Peptides from PV samples were labeled with 113, 115 and 117 iTRAQ reagents and peptides from CT samples with 118 and 121.…”
mentioning
confidence: 99%
“…Many cytoplasmic proteins are reduced in number by enucleation and vesiculation during maturation of reticulocytes [29,30]. In addition, the process of aging-associated vesiculation results in the specific removal of both cytosplasmic proteins such as modified hemoglobins and damaged membrane proteins such as band 3 [31].…”
Section: The Red Blood Cell Cytoplasmmentioning
confidence: 99%